Mobile Flood Assistant (MO-FA): Assisting flood victims with mobile technology - Md Din, Marina; Yussof, Salman; Abu Bakar, Muhammad Rasul (2017)
This paper presents the features and architecture of a mobile-based application that is developed to assist flood victims and rescue teams in search and rescue operations.Mobile Flood Assistant (Mo-FA) is an integrated Android-based mobile application to assist Malaysian citizens who live in flood prone areas with an early warning alert and to facilitate the current practice in search and rescue operation.Mo-FA consists of 2 main modules namely Flood Information and Notification Module, and e-SOS Module.The Flood Information and Notification Module aims to provide early warning to the public on possible flood occurrence.It is also able to provide flood-related information such as the amount of rain and river water level using the data obtained from Department of Irrigation and Drainage (DID). Relevant information such as the nearest evacuation centers and routes will be displayed on a map to facilitate affected victims to move to a safe area. The second module aims to facilitate the rescue teams to locate the victims’ whereabouts upon receiving SOS message sent by the victims.Considering the fact that mobile phone is a device which we keep close to us at almost all the time, Mo-FA could become a perfect tool to provide various flood related information and to provide a method for quick information distribution to the public and rescue teams.